Predicting well-being from personality in adolescents and older adults - Butković, Ana (Array, 2012)
The relationship between personality and well- being is dynamic and therefore should be examined within aging perspective. In study presented here we compared the prediction of well-being from personality in two samples–223 adolescents attending high-school (16–19 years ; M = 16.94, SD = 0.51) and 134 older adults (54–90 years ; M = 77.20, SD = 7.39) living in retirement home or at home. Different aspects of well-being were included in the study. Subjective well-being was measured with Index of Well-Being, but also self- esteem and loneliness were included as measures of psychological well-being. Personality (measured with FFPI ; Hendriks et al. in Pers Individ Dif 27:307–325, 1999) significantly predicted indicators of well-being (Self-Esteem, Loneliness and Index of Well-Being) in both samples, with emotional stability and extraversion as most pronounced predictors. Personality explained more variance of well-being in adolescents than in older adults, and more variance in eudaimonic than hedonic aspects of well-being.